Perfil das pme’s calçadistas da região do cariri cearense: Uma contribuição ao desenvolvimento regional - Tavares, Frederico Maia [UNESP]; Muniz, Jorge Muniz [UNESP]; Valladares, Paulo Ségio de Almeida; Pinto, Sidney de Lima; Guimarães, José Leonardo da Silveira (My University, 2015)
There is an important footwear cluster in Ceará Cariri which has shown higher than the national average in the industry growth region. The cluster is composed mostly of Small and Medium Enterprises (SMEs). Difficulties are common to any small and big company qualification of manpower and trainability. This article aims to understand the process of management of SMEs in the footwear cluster of Ceará Cariri and help to identify problems and opportunities for growth that can guide public policies to strengthen it, and the definition of strategies for improving competitiveness and regional development. To diagnose the Learning to Grow method, which focuses on technology, innovation and identification of growth opportunities (NORTH; SILVA; CALLE, 2013) was used. Interviews with owners and directors of nine (9) companies of that cluster, contributing to the process of managing these companies were made.
Profile of SMEs footwear region of cearense cariri: A contribution to regional development
Keywords: Cluster; Footwear; Management; Small and medium enterprises